Managerial Recommendations Improving the Competitive Capability of Firms Based on Total Quality Management during Covid-19 Pandemic - Ha Van Son; Nguyen Van Trai; Phan Thanh Tam (Ital Publication, 2022)
In 2021, the COVID-19 epidemic affected many aspects of the provinces' socio-economic fields, especially deeply affecting businesses at enterprises. The task of ensuring social security continues with the management agencies, who need appropriate solutions and support policies to encourage and help enterprises return to production and trade after the quarantine society quickly. The basis for management theory has contributed to improving the competitive capability based on improving Total Quality Management (TQM), such as the